Educomunicación para la paz: una estrategia digital para visibilizar procesos organizativos del distrito de Aguablanca, Cali (Colombia) [Dossier: Comunicación comunitaria, mediaciones digitales y soberanía tecnológica] - Tobar Tovar, Carlos Andrés (2026)
This research presents a digital communication strategy to highlight peacebuilding practices in communes 13 and 14 of the Aguablanca district, Cali, Colombia. It revisits the perspective of educommunication and the notion of peace “from below” to propose alternative narrative experiences to those developed by the hegemonic media. To this end, digital textualities were created based on the musical “Dónde meter la Cabeza” and the report “Garza Real,” which are the result of co-creation processes with the participating communities. The research concludes that educommunication is compatible with civic education processes aimed at peacebuilding and that strategies are needed to help communicate community efforts for a possible and desirable coexistence, taking into account the understanding of the context and expectations for social change. To this end, the research contributes to the creation of Habitancia Transmedia, an educational medium for learning about possible and desirable coexistence.